2014
DOI: 10.1590/0104-1169.3172.2405
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and risk classification protocol for patients in emergency units

Abstract: Objective to develop, validate the contents and verify the reliability of a risk classification protocol for an Emergency Unit. Method the content validation was developed in a University Hospital in a country town located in the state of Sao Paulo and was carried out in two stages: the first with the individual assessment of specialists and the second with the meeting between the researchers and the specialists. The use of the protocol followed a specific guide. Concerning reliability, the concordance or equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 13 publications
0
11
0
3
Order By: Relevance
“…The efficiency of the emergency and urgency network is dependent on a quality reception. In this way, it is possible to analyze whether the search for the service was necessary (14) . SMCR correlates the risk to a color, and a maximum time to offer medical attention is determined (13) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficiency of the emergency and urgency network is dependent on a quality reception. In this way, it is possible to analyze whether the search for the service was necessary (14) . SMCR correlates the risk to a color, and a maximum time to offer medical attention is determined (13) .…”
Section: Discussionmentioning
confidence: 99%
“…SMCR correlates the risk to a color, and a maximum time to offer medical attention is determined (13) . Most elders were classified as yellow, which indicates urgent situations, in which the patient needs care as quickly as possible, but there is not an immediate risk of life (14) , which leads to the belief that these patients are not seeking service without a real need. Falls are among the main causes of morbidity and mortality in the elderly population (17) , and are considered one of the most common reasons for hospitalization in this age group (8) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor is the use of the proposed protocol in the clinical context, which may point out difficulties and suggest improvements [24].…”
Section: Discussionmentioning
confidence: 99%
“…There is a study which indicates the need for training nurses in triage, since it was observed that the greater the professional qualification and the higher the number of hours performing triage, the more reliable the results in prioritization of care (13) . In this regard, the literature points out that health professionals working in emergency units need to develop skills that ensure technical and scientific competence as well as an embracing and humanized approach toward patients (5,14) .…”
Section: Introductionmentioning
confidence: 99%